Caracterización físico-química de la cascarilla de cacao (Theobroma cacao), para uso en la alimentación animal - Viveros Riofrio, Karla Jacqueline (2024)
The current research examined the physical and chemical properties of cocoa husks as a potential animal feed source, focusing on two varieties of cocoa cultivated in the province of El Oro: national and CCN51. Given the growing interest in the use of agro-industrial by- products for animal feed, the objective of this study was to evaluate their nutritional properties and their viability as an ingredient in animal diets. A completely randomized design was used and samples (1 kg) of cocoa husk obtained in the province of El Oro were taken; the physical properties evaluated were: water-holding capacity, bulk density, and moisture. For the chemical evaluation, a bromatological analysis of the samples was conducted on a dry basis. This analysis included the determination of pH, acidity, dry matter, ash content, protein, and ether extract. Moreover, the crude fiber, neutral detergent fiber, acid detergent fiber, and acid detergent lignin were also analyzed. The results showed no significant statistical differences (p>0.05) in most of the indicators evaluated, except for the bulk density variables, which did show statistical significance. The data collected were analyzed using the statistical program InfoStat. The results demonstrated that the national cocoa husk exhibited superior performance in terms of physical properties. However, regarding chemical composition, the national variety showed higher levels of acidity, dry matter, and crude fiber content. On the other hand, the CCN51 variety stood out for its higher content of pH, ash, crude protein, ethereal extract, neutral detergent fiber, acid detergent fiber, and acid detergent lignin. Therefore, this by-product presents acceptable nutritional value and can be considered a viable alternative for animal feed, with an outstanding potential for inclusion in ruminant diets.